Stabilization of a non-aqueous self-double-emulsifying delivery system of rutin by fat crystals and nonionic surfactants: preparation and bioavailability study. Issue 7 (22nd June 2017) - Wang, Qiang; Huang, Juan; Hu, Caibiao; Xia, Nan; Li, Tong; Xia, Qiang
Abstract : The use of a dual emulsifier system enhances emulsion stability and the non-aqueous SDEDS improves the oral bioavailability of rutin. Abstract : Literature examples of non-aqueous Pickering emulsions stabilized by fat crystals are very rare. Moreover, the applications of rutin are limited due to its low solubility in both water and oils (less than 0.10 mg g −1 and 0.25 mg g −1, respectively). Thus, herein, we developed an optimum formulation of a non-aqueous self-double-emulsifying delivery system (SDEDS) containing rutin and evaluated its oral bioavailability. The new formulation stabilized by fat crystals (glycerol monostearate, GMS) and nonionic surfactants was prepared via a two-step emulsification process. The presence of a mixture of GMS crystals and nonionic surfactants effectively improves the stability of the emulsions. The non-aqueous SDEDS spontaneously forms oil-in-oil-in-water (O/O/W) double emulsions in the gastrointestinal environment with the inner oil phase mainly containing the active ingredients. It is stable at both 4 °C and 25 °C for 30 days and could enhance the dissolution properties of the active ingredients. Furthermore, the protection of rutin against digestion-mediated precipitation was observed when the formulation contained a high concentration of GMS crystals. The oral absolute bioavailability of rutin obtained from SDEDS (8.62%) is 1.76-fold higher than that of the actives suspension (4.90%). Thus, the non-aqueous SDEDS is an attractive candidate for the encapsulation of water-insoluble and simultaneously oil-insoluble nutrients (such as rutin) and for use in oral delivery applications.